2014
DOI: 10.4103/2224-3151.206752
|View full text |Cite
|
Sign up to set email alerts
|

Universal access to medicines: evidence from Rajasthan, India

Abstract: India has outlined its commitment to achieving universal health coverage and several states in India are rolling out strategies to support this aim. In 2011, Rajasthan implemented an ambitious universal access to medicines programme based on a centralized procurement and decentralized distribution model. In terms of the three dimensions of universal health coverage, the scheme has made significant positive strides within a short period of implementation. The key objectives of this paper are to assess the likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 1 publication
0
34
0
Order By: Relevance
“…There has been an initiative in terms of free drug policy, from state governments such as that of Rajasthan, Tamil Nadu and Kerala, the replication of which in other states could have far reaching impact. Drug procurement models in these states in terms of mixed procurement system i.e., centralized procurement and distribution have resulted in lowering of purchasing price, better availability and utilization, and reduction in OOP expenditure [ 36 ]. When compared with other illnesses, distress financing ranged from 38% to 42.6% in case of heart disease and cancer respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been an initiative in terms of free drug policy, from state governments such as that of Rajasthan, Tamil Nadu and Kerala, the replication of which in other states could have far reaching impact. Drug procurement models in these states in terms of mixed procurement system i.e., centralized procurement and distribution have resulted in lowering of purchasing price, better availability and utilization, and reduction in OOP expenditure [ 36 ]. When compared with other illnesses, distress financing ranged from 38% to 42.6% in case of heart disease and cancer respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Government should consider increasing their level of spending encouraging the public health services and improve availability of medicines in public facilities. Provisioning of free medicines in public facilities not only becomes effective in providing financial protection, these play crucial role in improving efficiency of health systems [39].…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Nearly, 55% of both mothers and fathers of the children are educated more than primary, while nearly 14% of mothers work outside the house. According to 90% of the mothers of the sample, there is sufficient food at their house, thus representing a food-secure environment.Applying the above mentioned concept ofSelvaraj et al (2014), we have found that overall 48.46% of children go to ICDS and the rest do not. However, in terms of depth of services, it is found that even after reaching AWCs, not all services, which are expected to be provided, are actually received by the children(Table 1).…”
mentioning
confidence: 93%
“…For evaluation of any public policy, one should highlight three dimensions: breadth of the program (population covered), depth of the coverage (services offered), and height of the coverage (risk protection provided; Selvaraj et al, 2014;Asher & Bali, 2015). There is clearly a research gap on identifying the depth of the program of ICDS and its impact on reduction of child stunting of the program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation